Does merger & acquisition (M&A) strategy matter? A contingency perspective. Issue 6 (December 2022) - Angwin, Duncan N.; Urs, Uma; Appadu, Naaguesh; Thanos, Ioannis C.; Vourloumis, Stavros; Kastanakis, Minas N.
Abstract: This paper takes a contingency approach to investigate whether there are market performance variations for different types of M&A. Eight different types of M&A are identified in a typology based upon the conjunction of three contextual dimensions: external environmental, acquiring firm level strategy and CEO motivation. Drawing upon a sample of 1, 926 domestic UK deals we evaluate the typology to determine whether the financial markets distinguish between different types of M&A. Results indicate significant market and risk-adjusted performance differences by M&A type. These confirm that a contingency approach to M&A performance has merit. We suggest that the proposed integrated typology, that recognizes the importance of multiple aspects of strategic fit to M&A performance, addresses the paradox that M&A practitioners continue to pursue deals despite widespread acceptance that they result in high failure rates.